Karyotype analysis in Machaerium lunatum (Linn. f.) Ducke - I.G. Ugiomoh; C Ekeke (Journal of Applied Sciences and Environmental Management, 2018)
The paper gives an account of the results of karyological investigation on Machaerium lunatum (Linn. f.) Ducke using root squash technique. Root tips (approximately 1 cm) were excised and pretreated in 0.002M 8-hydroxyquinoline for 3–3.5 hrs, fixed in 3:1 ethanol-acetic acid for 24 hrs, hydrolised with 5% HCl and squashed in drops of FLP orcein on clean glass slides. Mitotic chromosome slides were observed under research microscope and photomicrographs of 10 good quality metaphase plates were taken and recorded. A chromosome number of 2n = 30 was recorded for the taxon and the chromosomes varied from 0.83 – 2.71 μm in length with karyotype of 7m+4sm+4st. The length of the long and short arms ranged from 0.64 – 1.66 μm and 0.19 – 1.05 μm respectively. The chromosomes varied from metacentric to subtelometacentric. This is the first report of the karyotype and chromosome of this species from Nigeria.